Disability and Child Protection - Flynn, Susan (My University, 2024)
The intention for this chapter is to offer a high-level overview of key issues at the intersection of child protection and disability. Owing to an expanding body of research, it is clear that disability presents unique and significant complexities and concerns in a child protection context
Palgrave Encyclopedia of Disability
PUBLISHED
Keywords: Child protection; Disability and child protection